The development of an experimental technique to measure the influence of temperature on the mechanical properties of weldments - Singh, Kashir (Department of Mechanical Engineering, 2019)
In large industries, such as in power stations, welds are widely employed to join different components together to meet various property requirements. The thermal gradient that develops during welding causes an inhomogeneous distribution of material properties, in areas adjacent to the weld, known as the Heat Affected Zones (HAZ). Welded joints subjected to elevated temperatures and loads during operations often experience a degradation of mechanical properties and performance of the joint. Studies have found that mechanical phenomena’s such as, fatigue and creep have compromised the structural integrity of weld zones. In essence a welded component acts as a composite material, for which it’s overall performance is dependent on its weakest material component. This study focuses on developing an experimental technique that is capable of measuring the influence of temperature on the mechanical and material properties across a weldment. The development of the experimental technique includes the design and optimisation of the hot zone of a welded tensile specimen, identification and characterisation of the different weld zones as well as, refining a strain recording strategy to detect the localised strains in each of the different weld zones. The application of the experimental technique is applied to welded components from turbine steam penetrations, which were extracted from a coal fired power station. The steam penetrations are a low Cr structural steel; (Cr 0.66, C 0.24 by wt. %) and have been in service for approximately 24 year (± 212 000 hrs). Two primary systems namely the Gleeble 3800 thermo-mechanical simulator and digital image correlation are used in this study. In order to accurately map the in-service evolution of material properties, each of the welds were mechanically loaded in tension and exposed to elevated operating temperatures. To induce mechanical loading at constant elevated temperatures, a Gleeble 3800 thermo-mechanical simulator with a tensile module was used to deform specimens at a strain rate of 50 µε.s1 . Experiments were conducted at various temperatures, ranging from room temperature (RT) to 535 o C. The evolution of material properties across the weldment was evaluated using Digital Image Correlation (DIC). DIC is a non-contact digital technique, capable of measuring localized strain during mechanical loading at elevated temperatures. In order to investigate the localized strain across the different weld zones, virtual strain gauges of one millimetre in length were simulated at intervals of one millimetre. It was found that there was a continuous accumulation of strain from the Fusion Line (FL) into the Parent Material (PM). This finding suggested that the HAZ nearest to the PM; which was the Fine Grained Heat Affected Zone (FGHAZ) was the weakest zone as it strained the most. The FL was found to be the least ductile region of the weld as most of the absorbed thermal energy provided during the welding process was used for strain hardening. At elevated temperatures, localised strain occurred at lower strain values than those at RT. This finding suggested that at elevated temperatures there was more thermal energy available for dislocation activation and mobilization. The influence of temperature on the local weld zones were evaluated by extending a specimen, containing just the parent material. A simulation of a virtual strain gauge across the monolithic specimen’s gauge length, revealed that necking occurred at the centre of the specimen which corresponded to the hot zone. In contrast, a simulation of virtual strain gauges across both welds revealed that necking occurred in the region between the HAZ and weld material. This finding inferred that the presence of a weld reduced the strength of the component, as the weld material was the weakest material. Furthermore, the in-service operating conditions was found to have significantly influenced the material behaviour of the welds. A weld that was exposed to a more elevated temperatures and loads, was found to have undergone a higher degree of material degradation, and strained to a larger extent when compared to a weld that was exposed to a more moderate operating environment.